Neonatal urinary tract infections: Analysis of the patients and recurrences - (:unkn) unknown (WILEY, 2004)
Background: Early diagnosis and proper treatment, including long-term follow up, are very important for neonatal urinary tract infections (UTI). Methods: The present study reports the analysis and long-term follow-up results of 71 newborns treated for UTI. Results: Forty-one per cent of patients were preterm babies. Suspected sepsis and hyperbilirubinemia were the main presenting features. Community-acquired and nasocomial UTI accounted for 63% and 37% of cases, respectively. The leading causative agents were Escherichia coli for community-acquired UTI and Klebsiella pneumoniae for nasocomial UTI. The urosepsis rate was 5%. Abnormal ultrasonography findings were present in 23% and vesicoureteral reflux was present in 15% of babies. A total of 23% of patients showed renal photopenic areas on dimercaptosuccinic acid scan. The recurrence rate was 28% occurring between 1.5 and 12 months, in particular in the first 6 months. Most of the recurrences developed in patients with no predisposing abnormalities. Conclusion: Pediatric nephrologic follow-up of babies experiencing UTI in the neonatal period is very important to identify the predisposing congenital abnormalities and scarred kidneys, to diagnose and to treat the recurrences earlier.
Keywords: causative agents; newborn; recurrences; urinary tract infections; FOLLOW-UP; CHILDREN; PYELONEPHRITIS; SCINTIGRAPHY; INFANTS; DAMAGE